Avaliação dos efeitos das frações do extrato etanólico das folhas da Morus nigra L. (amora) em animais com hipoestrogenismo. - MARANHÃO, Marina Cristine Silva (2023)
The transition between reproductive and non-reproductive stages in a woman's life is called climacteric, this involves a myriad of physical, endocrine and psychological changes that are influenced by ethnic, psychological and sociocultural factors. For the treatment of these outcomes, hormone replacement therapy (HRT) is used, however, there are several side effects, with contraindications, such as previous treatment of hormone-dependent tumors and history of previous thromboembolic events. Alternatives to HRT include herbal medicines such as Morus nigra L., a plant species used to combat menopausal symptoms, whose leaves contain phytoestrogenic substances. This study was of the randomized experimental type, with the experimental protocols approved by the CEUA of the Federal University of Maranhão. The objective of this work was to evaluate the effect of the chronic treatment of the aqueous (FAQ) and ethyl acetate (FACET) fractions of Morus nigra L. leaf extract in animals with hypoestrogenism. For the experiments, rats of the species Rattus norvegicus, Wistar strain and female Mus musculus Swiss strain mice, from the Central Animal Facility of the Federal University of Maranhão (UFMA), with weights ranging from 250 - 300 g and 25-35g, respectively, were used. For this, the animals were divided into 05 groups, using 05 animals per group: False operated (SHAM); Saline-treated ovariectomized patient (OVX-SAL); Ovariectomized treated with an aqueous fraction of 100 mg/kg (OVX-FAQ); Ovariectomized patient treated with 400 mg/kg acetate fraction (OVX FACET); Ovariectomized patient treated with estrogen associated with medroxyprogesterone 1 mg /Kg (OVX-E2+P). During treatment (30 days) the estrous cycle, body weight and body temperature were measured. At the end, the serum and hormonal biochemical parameters of the samples were evaluated. The OVX-SAL group exhibited a significant negative change in body weight, total fat, lipid profile and in different hormone markers, eg estradiol and FSH. A significant increase in skin temperature and reduction in serum calcium levels was also found compared to the SHAM group. Changes in the estrous cycle and uterine atrophy were also observed. The OVX-E2+P group significantly improved these deleterious effects of hypoestrogenism compared to the OVX-SAL group. On the effect of treatment with fractions of M. nigra in relation to body weight and total fat, it was observed that this significant reducing effect with the two fractions of M. nigra. In addition, the positive effect on the lipid profile of the animals that received the two fractions of M. nigra was remarkable. However, the OVX-FACET group was more efficient in controlling hot flashes, fat accumulation, lipid and hormonal profile. Thus, it is concluded that the two fractions of M. nigra have beneficial anti-osteoporotic, anti-dyslipidemic and anti-atherosclerotic effects. However, more studies should be carried out regarding the effect of estrogenic activity on the main symptoms of menopause. Keywords: